Rapid decline of carbon monoxide emissions in the Fenwei Plain in China during the three-year Action Plan on defending the blue sky. (1st July 2023) - Jia, Mengwei; Jiang, Fei; Evangeliou, Nikolaos; Eckhardt, Sabine; Huang, Xin; Ding, Aijun; Stohl, Andreas
Abstract: The Fenwei Plain is one of China's most polluted regions, with poor atmospheric dispersion conditions and an outdated energy structure. After implementing multiple policies in recent years, significant reductions in air pollutant concentrations were observed. In this study, based on the Lagrangian-Bayesian inversion framework FLEXINVERT, we constructed a variable resolution inversion system focusing on the Fenwei Plain and inferred the carbon monoxide (CO) emissions using in-situ atmospheric CO observations from April 2014 to March 2020. We analyzed the spatiotemporal variations of the CO emissions and discussed their causes, especially the effect of the "Three-year Action Plan on Defending the Blue Sky" (TAPDBS). Before the policy, CO emissions temporarily increased, and the overall decrease in CO emissions per unit of Gross Domestic Product (GDP) slowed down. When the policy was implemented, CO emission fluxes declined sharply, with an average drop of 28%, accompanied by an even higher 37% decrease of CO emission per GDP. The reasons for the decline in CO emissions in Shanxi, Shaanxi and Henan are diverse. The decrease in energy intensity is the reason for CO emission reduction in Shannxi and Henan province but not in Shanxi province. This research fills the gap in emission information in recent years and confirms that TAPDBS has brought a breakthrough in both economic development and air quality protection in the Fenwei Plain. Graphical abstract: Image 1 Highlights: Based on the CO measurements, the CO emission in the Fenwei Plain was constrained. CO emissions decreased by 28% in the polluted season of 2019 compared to the pre-2019. The reasons for CO emission reduction in Shanxi, Shaanxi and Henan are discrete.